Cancer evolution and immunity in a rat colorectal carcinogenesis model - Vannucci, Luca; Fiserova, Anna; Horvath, Ondrej; Rossmann, Pavel; Mosca, Franco; Pospisil, Miloslav (International journal of oncology, 2004)
Tumor development is modulated by the interplay between the transformed cells and the host, and produces changes in the immune system. We followed the cancer progression and the variation of immune parameters in a rat in vivo model of induced colorectal carcinoma. Retrospective data collected from different experiments illustrated the dynamics of the tumor development, and of the immune cells (NK, NKT, T, CD4+, CTL, B and gammadeltaTCR+ cells), cytotoxicity, and CD4/CD8 ratio, at the third, sixth and eighth month of carcinogenesis. The chemically-induced carcinogenesis involved the complete large bowel, with progressive generation of multiple tumors during the complete considered period. Reduction in number and function of cytotoxic and regulatory cells of the innate immunity were crucial for cancer progression.
Keywords: Cytotoxicity, Immunologic; CD4-CD8 Ratio; Immunity; poměr CD4 a CD8 lymfocytů; krysa rodu Rattus; zvířata; T-lymfocyty - podskupiny; potkani Wistar; imunita; buňky NK; Killer Cells, Natural; T-Lymphocyte Subsets; Receptors, Antigen, T-Cell, gamma-delta; Rats, Wistar; kolorektální nádory; receptory antigenů T-buněk gama-delta; Male; cytotoxicita imunologická; Rats; Animals; mužské pohlaví; Disease Models, Animal; Colorectal Neoplasms; modely nemocí na zvířatech